THE MOST COMMON INJURIES AMONG BASKETBALL PLAYERS AND THEIR PREVENTION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides an in-depth analysis of injuries in basketball players, their prevention methods, and rehabilitation processes. Basketball is a high-intensity sport in which athletes are constantly exposed to various types of injuries. The article analyzes the most common injuries and discusses their causes and consequences from a scientific perspective. In particular, knee, wrist, ankle, muscle and tendon injuries, as well as back and waist problems, are considered. It also emphasizes the importance of physical preparation, proper technique, protective equipment, and pre-workout warm-up methods to prevent injuries. The article provides a detailed description of the stages of injury treatment, and examines the importance of physiotherapy, physical recovery exercises, and psychological preparation. Scientifically based recommendations are given on how the rehabilitation process should be carried out to shorten the basketball player's return to sports and reduce the likelihood of injury recurrence. This study aims to explore important strategies that help athletes maintain long and successful careers, providing useful information for sports doctors, coaches, and athletes themselves.